Pengaruh Penerapan Sistem E-Filling, Tingkat Pemahaman Perpajakan Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Natalia, Neli Rosa; Barli, Harry (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2025)
This research aims to test whether there is an influence of the implementation of the e-filling system, the level of understanding of taxation and tax sanctions on individual taxpayer compliance. The population in this study were employees who worked at PT Sumber Alfariya Trijaya Branch Parung in the Pesanggrahan District area. The number of samples in this study was 55 respondents. The sampling technique uses the convenience sampling method. The research method used is quantitative with the data source in the form of primary data. The data analysis method uses validity tests, reliability tests, then classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests and multiple linear regression tests. Hypothesis testing uses the coefficient of determination test, F test with SPSS version 27. The results of this research provide empirical evidence that partially the variables of implementing the e-filling system and the level of understanding of taxation have a significant effect on individual taxpayer compliance, and the tax sanctions variable has no effect on individual taxpayer compliance. Simultaneously, the variables implementing the e-filling system, the level of understanding of taxation and tax sanctions have a significant effect on individual taxpayer compliance